Penerapan Akad Wadiah Yad Dhamanah dalam Tabungan Sekolah - Mutmainnah, Mutmainnah; Susanti, Susanti; M. Holil Baita Putra (Program Studi Ekonomi Syariah IAIN Parepare, 2024)
Implementation of children's savings provided by the school with daily savings without limiting the minimum amount to be saved. So that it makes it easier for the guardians of students and students to set aside or save their money according to their desired targets and needs. This research uses a qualitative approach because the data collected is in the form of words and images. The implementation of children's savings at Madrasah Al-Amin applies to all female students starting from class 0-VI and they are required to have a savings book. This was also expressed by Ustadzah Hoiriyah in his interview that the requirements for being able to save are: